Teaching STEM to first generation college students : a guidebook for faculty & future faculty - Horowitz, Gail (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
"Some students come to college knowing the ropes, knowing what it takes to be successful as STEM students. But many do not. Research shows that students who are the first-generation in their family to attend or complete college are likely to arrive at your classroom not knowing what it takes to be successful. And data shows that more first-generation students are likely to be arriving on your doorstep in the near future. What can you do to help these students be successful? This book can provide you with some quick, easy, and effortless steps that you can take to help first-generation college students succeed without having to change the way you teach. Why put in this effort in the first place? The payoff is truly worth it. First-generation college students are frequently low-income students and from ethnic groups underrepresented in STEM. With a little effort, you can enhance the retention of underrepresented groups in your discipline, at your institution and play a role in national efforts to enhance diversity in STEM"--